Analysis of Cost-benefit and CO2 Emissions of Solar Energy-Intelligent Poultry Feeding System: Application of NPV and Dynamic Environmental I-O Model - Yang, Yu-Chen; Chiu, Yi-Chich; Hong, Cheng-Yih (International Journal of Energy Economics and Policy, 2019)
Intelligent Poultry Feeding System is the future development trend of agriculture. This is the production model of big data platform through technological innovation such as IOT, AI, etc. In recent years, Taiwan has proposed the Agricultural 4.0 program to combine renewable energy with technological innovation to promote the development of agriculture. Building a complete intelligent poultry house including solar power generation and Intelligent Poultry Feeding System, the purpose of this paper is to evaluate the effectiveness of this policy and analyze the economic effects and environmental protection of Solar Energy-Intelligent Poultry Feeding System. The research methodology uses the Net Present Value (NPV) for financial evaluation and the Dynamic Environmental I-O Model for energy. The results of this paper show that the investment of Solar Energy-Intelligent Poultry Feeding System can recover the investment cost within a reasonable period of time, and effectively improve the CO2 emission effect, achieving the dual tasks of industrial development and environmental protection. Keywords: Solar Energy, Intelligent Poultry Feeding System, NPV, Dynamic Environmental I-O Model JEL Classifications: Q19, Q43, C6. DOI: https://doi.org/10.32479/ijeep.8443